2022
DOI: 10.3390/nu14235092
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Resistin (−420C/G) Single Nucleotide Variant, Resistin Serum Concentration, Carbohydrate, and Lipid Parameters and Fried Food Taste Preference in Patients with Hypertriglyceridemia

Abstract: Background: Resistin is a proinflammatory adipokine involved in metabolic disorders. Its interplay with hypertriglyceridemia remains to be elucidated. We aimed to evaluate the relationship between resistin (−420C/G) single nucleotide variant (SNV) and metabolic parameters and preference for fried food consumption in hypertriglyceridemia. Methods: The study enrolled 179 hypertriglyceridemic (HTG) and 182 normotriglyceridemic (NTG) patients. Anthropometric measurements, serum resistin, insulin and fasting glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, studies have shown that fried foods can do more harm than good to human health, due to high calories(Pan et al 2021). Fried foods can be an important contributor to many diseases, such as obesity, high blood pressure, cardiovascular and cerebrovascular disease, and cancer(Pilar et 2012;Zhang et al 2023;Miller-Kasprzak et al 2022). Furthermore, aldehydes in the food form carcinogenic substances of group I under high temperature conditions, which are harmful to human body(Schouten et al 2023).…”
mentioning
confidence: 99%
“…However, studies have shown that fried foods can do more harm than good to human health, due to high calories(Pan et al 2021). Fried foods can be an important contributor to many diseases, such as obesity, high blood pressure, cardiovascular and cerebrovascular disease, and cancer(Pilar et 2012;Zhang et al 2023;Miller-Kasprzak et al 2022). Furthermore, aldehydes in the food form carcinogenic substances of group I under high temperature conditions, which are harmful to human body(Schouten et al 2023).…”
mentioning
confidence: 99%